Ambiguity Found In Backpack 4 English Textbook - Riscahyanti, Meltysari (2014)
This study deals with the ambiguity which is found in Backpack 4 English textbook. The aims of this study are (1) to describe the types of ambiguity found in Backpack 4 English textbook, (2) to describe the frequency of each type of ambiguity, (3) to describe the dominant type of ambiguity, (4) to describe the causes of ambiguity, and (5) to describe the way to disambiguate ambiguity. The type of this research is descriptive qualitative research. The data source of this research is ambiguous words, phrases and sentences found in Backpack 4 English textbook. The data collection technique is documentation. The technique of data analysis are descriptive qualitative. The writer uses the theories from Fauziyati, Kreidler, Robert, Roadman and Hyme to analyze the types of ambiguity. The result of this study shows that (1) the writer found three from four types of ambiguity namely: lexical ambiguity, referential ambiguity, and surface structure ambiguity; (2) the frequency of each type of ambiguity are 43 lexical ambiguity (24,57%), 74 referential ambiguity (42,29 %), 58 surface structure ambiguity (33,14 %), and 0 deep structure ambiguity (0%); (3) the dominat types of ambiguity is referential ambiguity; there are 74 ambiguous sentences or 42,29%; (4) the causes of ambiguity are without context, ambiguous word order, improper or missing punctuation, faulty sentence construction, ambiguous words, and faulty pronoun reference; and (5) the way to disambiguate ambiguity are using paraphrasing, truth conditional sentences, adding preposition, moving sentence construction, adding additional context, adding correct punctuation and using picture.